Graphene enhanced anchoring of nanosized Co3O4 particles on carbon fiber cloth as free-standing anode for lithium-ion batteries with superior cycling stability. (1st September 2017) - Xie, Qinxing; Zhang, Yufeng; Zhu, Yating; Fu, Weigui; Zhang, Xu; Zhao, Peng; Wu, Shihua
Graphical abstract: Highlights: Nanosized Co3 O4 particles were successfully anchored on graphene-coated carbon cloth. Graphene facilitates the anchoring of Co3 O4 on carbon fibers. The composite exhibits excellent rate performance as anode of LIBs. The composite exhibits superior cycling stability as anode of LIBs. Abstract: The graphene-coated carbon fiber cloth (CC@Gr) anchored with nanosized Co3 O4 particles was successfully fabricated. According to the results of structural characterization, it was observed that the graphene-coated carbon fibers are able to anchor much higher amount of Co3 O4 nanoparticles than graphene-free carbon fibers. The composite was applied as free-standing anode for lithium ion batteries, and it exhibits enhanced energy storage capability. A high reversible specific capacity of nearly 400 mAh g −1 at a current density of 100 mA g −1 can be achieved based on the total mass of Co3 O4 and CC@Gr fibers (mass ratio = 16:84). In addition, the composite demonstrates excellent rate performance and superior cycling stability.